Design and evaluation of an ultra-area-efficient fault-tolerant QCA full adder. Issue 6 (June 2015) - Roohi, Arman; DeMara, Ronald F.; Khoshavi, Navid
Abstract Quantum-dot cellular automata (QCA) has been studied extensively as a promising switching technology at nanoscale level. Despite several potential advantages of QCA-based designs over conventional CMOS logic, some deposition defects are probable to occur in QCA-based systems which have necessitated fault-tolerant structures. Whereas binary adders are among the most frequently-used components in digital systems, this work targets designing a highly-optimized robust full adder in a QCA framework. Results demonstrate the superiority of the proposed full adder in terms of latency, complexity and area with respect to previous full adder designs. Further, the functionality and the defect tolerance of the proposed full adder in the presence of QCA deposition faults are studied. The functionality and correctness of our design is confirmed using high-level synthesis, which is followed by delineating its normal and faulty behavior using a Probabilistic Transfer Matrix (PTM) method. The related waveforms which verify the robustness of the proposed designs are discussed via generation using the QCADesigner simulation tool.